Assessment Study On Wastewater Management In Latakia Hospitals - Abazli, Hicham; Jneidi, Hussein; Al-khateeb, Jamal; Hatem, Siba (Latakia University Journal -Basic Sciences Series, 2019)
Contamination resulted by hospitals wastewater is a major environmental and human health issue. Due to its significance, the competent authorities in Syria have set some regulations to ensure the safe management of liquid hazardous wastes discharged from hospitals. This study highlights these regulations and monitors reality of their implementation in a sample of Latakia hospitals using a questionnaire which was prepared depending on the content of related national guidelines. It has been concluded that these regulations are just wards on paper, as there isn’t any kind of monitoring for the discharges from hospitals, so they could pollute the underground and surface water as the hospitals are not connected to any municipal treatment plant. There is need, in all hospitals, to apply the minimum practices for the safe management of their liquid wastes, till they could operate their own wastewater treatment equipment.